THE IMPLEMENTATION OF POSITIVE BEHAVIOR SUPPORT THROUGH CHAMPS TO IMPROVE STUDENT BEHAVIOR - Lupita Jane Suwandi (Universitas Kristen Satya Wacana, 2019)
An effective classroom is one that runs smoothly with a few disruptions. In fact, based on the observation at grade 4 XYZ school, the researcher found that students frequently did inappropriate behavior such as calling out, excessive talking, forgetting to raise the hand quietly when asking question or stating an idea. One factor that made it happen was because the students did not clearly know about the teacher's behavior expectation. Facing these problems, the researcher decided to use a preventive way to minimalize the students' misbehavior using the CHAMPS approach which is a part of Positive Behavior Support. The purpose is to find out whether the students' behavior will be improved by the implementation of CHAMPS as an expectation before the lesson started. The method of this research was Classroom Action Research (CAR) which consisted of two cycles and involved 20 students. The instruments that used were the teacher's rating scale, student's attitude scale, and researcher's journal reflection. Descriptive statistical analysis and qualitative descriptive analysis were the technique used to analyze the data. From the data that has been analyzed, the researcher concluded that the implementation of Positive Behavior Support using CHAMPS had been improved student behavior in the classroom, specifically in their compliance towards the classroom rules and procedures. In short, despite its weaknesses and limitation, CHAMPS can be an alternative to minimalize students' misbehavior and improve students' behavior in the classroom.